Soil resource inventory for integrated land management planning: Geo-spatial approach - GAHLOD, N. S.; KHUSPURE, JAYSHREE; JARYAL, NAVNEET; KUMAR, MUNISH; ARYA, V. S. (Journal of Soil and Water Conservation, 2018)
Remote Sensing & Geographical Information System (RS&GIS) is the backbone for planning and management. Essentially it seeks to integrate a large volume of spatial and non-spatial information about various facets of natural resources. The present study was undertaken to identify the different physiographic units, landforms and soil resources to assess the topography, slope, climate and land use as an external land feature. IRS-ID, LISS-III Satellite data was used to delineate different physiographic units using image interpretation keys on 1:50,000 scale along with exhaustive ground truthing. The main physiographic units identified in the study area were river terraces, uplifted river terraces, mountain tops and undifferentiated mountain slope and narrow mountain valleys. Landscape wise distribution of area illustrate that major part of district falls under complex landscape where in soils developed on rocks namely phyllite, schist, gneiss and quartzite etc., covering an area of 55.8% of TGA, followed by slate having 2.58% and alluvio-colluvial material having 0.14% area of district. Physiographically, the area under undifferentiated mountain slopes were found to cover 58.59% followed by uplifted river terraces covering 0.14%, valley 0.06% of the district and classified as Entisols, Inceptisols, Alfisol and Mollisols. The major part of area found under forest was 2,60,093 ha. Area under open scrub and agriculture recorded as 129158 and 69508 ha, respectively. Remaining area of district was parted by miscellaneous uses, among them about 41.04% area was under snow covered lands followed by waterbodies (0.37%), rock out crop (0.02%) and habitation (0.004%).